1969
DOI: 10.1128/jb.97.1.350-361.1969
|View full text |Cite
|
Sign up to set email alerts
|

Shear-oriented Microfibrils in the Mucilaginous Investments of Two Motile Oscillatoriacean Blue-Green Algae

Abstract: Trichomes of two oscillatoriacean blue-green algae execute screw-like gliding motion, but the two organisms differ from each other with respect to the screw sense of motion. Electron microscopy of serial longitudinal sections reveals extracellular microfibrils which lie roughly parallel to streamlines at the surface of each organism. The author proposes that the microfibrils are oriented by shear in a zone just external to the outer unit membrane-like component of the cell wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1972
1972
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(8 citation statements)
references
References 52 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…Rotation of the fibrils could produce tiny undulations or oscillations discussed above that propel the filament. In fact, shearoriented microfibrils have been detected in the slime of two oscillatoriacean cyanobacteria (144). However, these fibrils may not be effective in propulsion.…”
Section: Mechanism Of Gliding Movementsmentioning
confidence: 99%
“…Rotation of the fibrils could produce tiny undulations or oscillations discussed above that propel the filament. In fact, shearoriented microfibrils have been detected in the slime of two oscillatoriacean cyanobacteria (144). However, these fibrils may not be effective in propulsion.…”
Section: Mechanism Of Gliding Movementsmentioning
confidence: 99%
“…(The "oscillatory" path of the end of an Oscillatoria filament is the two-dimensional, microscopic projection of its motion, which is actually spiral [1051.) (iii) The direction of flow of microfibrils in mucilage parallels the direction of filament movement (481).…”
Section: Cyanophagementioning
confidence: 98%
“…A layer of mucilage surrounds the cells or filaments of many bluegreen algae. In shadow micrographs (248,543,685, 708) and in thin sections (481,501,775), mucilage has a fibrillar appearance, but the presence of fibrils 30 A wide, and wider, may be due to binding together of individual fibrils by the act of drying (438). Chemical studies of presumptive mucilage are described in Table 3.…”
Section: Ii1mentioning
confidence: 99%
“…Previous studies have demonstrated that various cyanobacterial sheaths consist of a meshwork of polysaccharide fibrils which are variably oriented with respect to the cell surface. In some motile cyanobacteria the fibrils extend radially from the cell surface (13,15), whereas in other species a helical orientation has been demonstrated (14). However, until now, no reports have been published concerning the chemistry of these fibrils, which Frey-Wyssling and Stecher (7) thought to be cellulose in the genus Nostoc.…”
mentioning
confidence: 99%